Design of an Online GWEP Test Application to Assess English Proficiency of Students at Horizon University Indonesia: Penelitian - Wafiqah Yasmin Azhar; Anwar Hilman; Arif Budimansyah Purba; Wahyudi; Vivi Ayu Lestari; Ahmad Najib Mutawally (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
English proficiency is an essential skill in both academic and professional settings. To support this need, Horizon Indonesia University currently uses the EFSet as an evaluation tool in its Global Workplace English Program (GWEP). However, EFSet has several limitations, including inflexible navigation, fixed question formats, and less informative result reports. This study aims to design a more user-friendly UI/UX for the GWEP online test application that better meets the needs of both students and lecturers. The research applies a Design Thinking approach and uses a mixed-methods strategy (qualitative and quantitative) through surveys, interviews, observations, and prototype testing with Figma. The results show that the new application offers easier navigation, a “mark question” feature, and more detailed result reports. A total of 90% of users completed the test without issues and in less time compared to EFSet. This application is expected to serve as a more effective alternative for assessing English proficiency online.